Unexpected Islands in a Sea of Information Space in the Age of Globalization - Pedragosa, Pau (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2012)
Since the late 90s of XXth century the global dissemination of new electronic technologies of information are accelerating a cultural and social revolution that can even lead to an epochalchange. The purpose of this article is to understand our new "information society" from the point ofview of the concept of space, in order to trace the outlines of the new cultural topology. I propose tounderstand this new "topology of culture" through one of the most important philosophies of thetwentieth century, the classical phenomenology of Husserl and Heidegger, and its critical reception made by Peter Sloterdijk, as well as through the so called "information theory". Space is always more than just physical space, it is also a lived space with which we expres an understanding of our "beingin the world". Early Modernity conceptualized space as a geometric abstraction and built it with thenew industrial technology. This technology interpreted our way of living in an abstract and universalworld.Iproposethatthenewspatialparadigmconstructedbythenewinformationtechnologiesconsistsonasetof"islands"or"bubbles"carriersofdifferent"lifeworlds",surroundedbya"sea"ofinformation.The essence of this topology is the recovery of the limit, absent in the geometric design of space. This limit is the interface or screen that filters information. It is what separates and unites redundancy and novelty.